1977
DOI: 10.1073/pnas.74.10.4528
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectricity and regeneration: large currents leave the stumps of regenerating newt limbs.

Abstract: Electrical currents near regenerating newt limbs were measured with a recently developed vibrating probe.Steady currents with local surface densities of 10 to 100 MA/cm2 or more leave the end of the stump during the first 5-10 days after amputation and are balanced by currents with densities of only 1-3 jA/cm2 that enter the intact skin around the stump. They are immediately dependent upn the entry of sodium ions into this skin and are therefore inferred to be skin-driven. The outward currents are comparable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(87 citation statements)
references
References 19 publications
4
82
0
Order By: Relevance
“…Patterning and size control during development and regeneration are also regulated by bioelectric signaling (52,(71)(72)(73)(74)(75)(76)(77)(78). Mutations in two strains of zebrafish with fin size phenotypes map to genes involved in bioelectric signaling (41,79).…”
Section: Discussionmentioning
confidence: 99%
“…Patterning and size control during development and regeneration are also regulated by bioelectric signaling (52,(71)(72)(73)(74)(75)(76)(77)(78). Mutations in two strains of zebrafish with fin size phenotypes map to genes involved in bioelectric signaling (41,79).…”
Section: Discussionmentioning
confidence: 99%
“…Na þ influx in the amputated newt limb and H þ efflux in the amputated tail of Xenopus tadpoles generate ionic currents across the wound epidermis essential for regeneration. Na þ influx is via sodium channels (Borgens et al, 1977). H þ efflux in the amputated tail is driven by a plasma membrane ATPase in the epidermal cells , and is likely to be important for limb regeneration as well, given that a gene encoding a v-ATPase was the most abundant clone in a suppressive subtraction cDNA library made from dedifferentiating axolotl limb tissue (Gorsic et al, 2008).…”
Section: Mechanisms Of Histolysismentioning
confidence: 99%
“…It is well documented that endogenous electric fields play a role in regeneration, and it has been shown that applied electric fields are able to enhance regeneration and repair in vertebrates (Borgens et al, 1977(Borgens et al, , 1981Kerns and Lucchinetti, 1992;McCaig et al, 2005). have recently demonstrated a molecular link between electric currents and tail regeneration in Xenopus.…”
Section: Electric Currents and Regenerationmentioning
confidence: 99%